Post penetrating keratoplasty glaucoma – A review - Gupta, P; Sharma, A; Ichhpujani, P (Nepalese Journal of Ophthalmology, 2014)
Glaucoma following penetrating keratoplasty remains a challenge for the treating ophthalmologist. Its frequent occurrence, difficult diagnosis and recalcitrant nature coupled with the propensity to cause irreversible visual loss makes it essential to identify the problem early and manage it effectively. A careful pre-operative assessment along with appropriate intra-operative measures can help to reduce the chances of developing glaucoma in the post-operative period. Wherever indicated, prompt therapy should be initiated to lower intraocular pressure and salvage vision. Effective management of post-operative keratoplasty glaucoma remains an enigma with no single therapy being suited for all cases. One has to weigh the risks and benefits of the anti-glaucoma drugs on the corneal graft. However, it should be kept in mind that although there is a potential option for a graft exchange, vision lost from glaucomatous optic nerve damage cannot be recovered. This review aims at highlighting the magnitude of the problem, assessing the risk factors that predispose to post-penetrating keratoplasty glaucoma along with the methodology for its diagnosis and management. DOI: http://dx.doi.org/10.3126/nepjoph.v6i1.10776 Nepal J Ophthalmol 2014; 6 (2): 80-90